Towards a critical sociolinguistics - Singh, Rajendra (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 1996)
This collection of twelve essays, some of which have been written specifically for this volume by well-known European and North-American sociolinguists, reflects an increasing recognition within the field that sociological and theoretical innocence can no longer be underwritten by it, and offers a multi-pronged and multi-methodological way to move towards a critical, reflexive, and theoretically responsible socio-linguistics. It explores, with courage and sensitivity, some very important areas in the enormous space between Bloomfieldian 'idiolect' and Chomskyan 'UG' in order to situate the hum.